Mandatory Medicare Bundled Payment Program for Lower Extremity Joint Replacement and Discharge to Institutional Postacute Care: Interim Analysis of the First Year of a 5-Year Randomized Trial - Finkelstein, Amy; Ji, Yunan; Mahoney, Neale; Skinner, Jonathan (JAMA : the journal of the American Medical Association, 2018)
Bundled payments are an increasingly common alternative payment model for Medicare, yet there is limited evidence regarding their effectiveness. To report interim outcomes from the first year of implementation of a bundled payment model for lower extremity joint replacement (LEJR). As part of a 5-year, mandatory-participation randomized trial by the Centers for Medicare & Medicaid Services, eligible metropolitan statistical areas (MSAs) were randomized to the Comprehensive Care for Joint Replacement (CJR) bundled payment model for LEJR episodes or to a control group. In the first performance year, hospitals received bonus payments if Medicare spending for LEJR episodes was below the target price and hospitals met quality standards. This interim analysis reports first-year data on LEJR episodes starting April 1, 2016, with data collection through December 31, 2016. Randomization of MSAs into the CJR bundled payment model group (75 assigned; 67 included) or to the control group without the CJR model (121 assigned; 121 included). Instrumental variable analysis was used to evaluate the relationship between inclusion of MSAs in the CJR model and outcomes. The primary outcome was share of LEJR admissions discharged to institutional postacute care. Secondary outcomes included the number of days in institutional postacute care, discharges to other locations, Medicare spending during the episode (overall and for institutional postacute care), net Medicare spending during the episode, LEJR patient volume and patient case mix, and quality-of-care measures. Among the 196 MSAs and 1633 hospitals, 131 285 eligible LEJR procedures were performed during the study period (mean volume, 110 LEJR episodes per hospital) among 130 343 patients (mean age, 72.5 [SD, 0.91] years; 65% women; 90% white). The mean percentage of LEJR admissions discharged to institutional postacute care was 33.7% (SD, 11.2%) in the control group and was 2.9 percentage points lower (95% CI, -4.95 to -0.90 percentage points) in the CJR group. Mean Medicare spending for institutional postacute care per LEJR episode was $3871 (SD, $1394) in the control group and was $307 lower (95% CI, -$587 to -$27) in the CJR group. Mean overall Medicare spending per LEJR episode was $22 872 (SD, $3619) in the control group and was $453 lower (95% CI, -$909 to $3) in the CJR group, a statistically nonsignificant difference. None of the other secondary outcomes differed significantly between groups. In this interim analysis of the first year of the CJR bundled payment model for LEJR among Medicare beneficiaries, MSAs covered by CJR, compared with those that were not, had a significantly lower percentage of discharges to institutional postacute care but no significant difference in total Medicare spending per LEJR episode. Further evaluation is needed as the program is more fully implemented. ClinicalTrials.gov Identifier: NCT03407885; American Economic Association Registry Identifier: AEARCTR-0002521.